2001
DOI: 10.1118/1.1359441
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use of flat‐panel imagers for radiotherapy verification (in English)

Abstract: This thesis investigates the feasibility of the application of flat‐panel imagers (FPIs) based on amorphous silicon to radiotherapy verification. Intensity modulated radiotherapy imposes new demands on verification procedures. A contrast resolution of 1% may be required from portal imaging systems to resolve the target structure and the organs at risk (OAR). Furthermore a spatial resolution of 1 mm is desired. The imaging characteristics, spatial resolution, efficiency, and noise characteristics of the FPI for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been established that a-Si EPIDs that employ high-Z scintillation screens such as Gd 2 O 2 S : Tb have an increased sensitivity to low energy ͑Ͻ1 MeV͒ photons. 3,[7][8][9][10][11] This is in contrast with the fairly linear response vs photon energy observed above 1 MeV where the Compton interaction dominates. Generally, EPID pixel values are calibrated against ion chamber readings in an open reference field where the energy spectrum is essentially that which exits the head of the linac.…”
Section: Introductionmentioning
confidence: 68%
“…It has been established that a-Si EPIDs that employ high-Z scintillation screens such as Gd 2 O 2 S : Tb have an increased sensitivity to low energy ͑Ͻ1 MeV͒ photons. 3,[7][8][9][10][11] This is in contrast with the fairly linear response vs photon energy observed above 1 MeV where the Compton interaction dominates. Generally, EPID pixel values are calibrated against ion chamber readings in an open reference field where the energy spectrum is essentially that which exits the head of the linac.…”
Section: Introductionmentioning
confidence: 68%
“…One option is to use the megavoltage linear accelerator ͑linac͒ as the CT radiation source in conjunction with a detector system to measure the transmitted fluences. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Online kVCT has been explored with an additional kV x-ray tube, [23][24][25] using CT-on-rails, 26 and with a dual-energy-capable linac head. 27 Their numerous differences aside, one characteristic com-mon amongst many of these systems is a limited field-ofview ͑LFOV͒.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the low-frequency drop of MTF pre of the investigated detector was caused by the scattered radiation created within the detector. One author observed the low-frequency drop experimentally for a flat panel imager (Groh 2001).…”
Section: Discussionmentioning
confidence: 99%